Respuesta :

[tex]5x^2+10x-40=5(x^2+2x-8)=5(x^2+4x-2x-8)=5[x(x+4)-2(x+4)]=5(x-2)(x+4)[/tex]

The Answer: B

:)
cher
5x² + 10x - 40

Let's go through all of the answers & simplify them, then see if they are correct.

A) 5(x - 4)(x + 2)

Simplify.

5x² - 10x - 40

So, A) is INCORRECT.

B) 5(x - 2)(x + 4)

Simplify.

5x² + 10x - 40

So, B) is the correct answer.

However, let's also check C just in case :)

C) 5(x - 4)(x - 2)

Simplify.

5x² - 30x + 40

Therefore C) is incorrect.

So, your correct answer is B) 5(x - 2)(x + 4)

~Hope I helped!~
Ver imagen cher